Pulmonary function changes in older adults with and without metabolic syndrome - Maysa Alves Rodrigues Brandao-Rangel (Nature Portfolio, 2021)
Abstract The low-grade inflammation associated with metabolic syndrome (MS) triggers functional and structural alterations in several organs. Whereas lung function impairment is well reported for older adult population, the effect of MS on functional and immunological responses in the lungs remains unclear. In this cross-sectional study we determined whether MS alters pulmonary function, and immunological responses in older adults with MS. The study sample consisted of older adults with MS (68 ± 3 years old; n = 77) and without MS (67 ± 3 years old; n = 77). Impulse oscillometry was used to evaluate airway and tissue resistance, and reactance. Biomarkers of inflammation and fibrosis were assessed in the blood and in breath condensate. The total resistance of the respiratory system (R5Hz; p < 0.009), and the resistance of the proximal (R20Hz; p < 0.001) and distal (R5Hz–R20Hz; p < 0.004) airways were higher in MS individuals compared to those without MS. Pro-inflammatory (leptin, IL-1beta, IL-8, p < 0.001; TNF-alpha, p < 0.04) and anti-inflammatory cytokines (adiponectin, IL-1ra, IL-10, p < 0.001), anti-fibrotic (relaxin 1, relaxin 3, Klotho, p < 0.001) and pro-fibrotic (VEGF, p < 0.001) factors were increased in sera and in breath condensate individuals with MS. The results show that MS adversely affect lung mechanics, function, and immunological response in older adults. The data offer a metabolic basis for the inflammaging of the lungs and suggest the lungs as a potential therapeutic target for controlling the immune response and delaying the onset of impaired lung function in older adults with MS.